Myotonic dystrophy kinase‐related CDC42‐binding kinase α, a new transferrin receptor type 2‐binding partner, is a regulator of erythropoiesis. Issue 4 (4th February 2021) - Richard, Cyrielle; Viret, Sophie; Cantero Aguilar, Lilia; Lefevre, Carine; Leduc, Marjorie; Faouzi, El Hassan; Azar, Nabih; Lavazec, Catherine; Mayeux, Patrick; Verdier, Frédérique
Abstract: Efficient erythropoiesis relies on the expression of the transferrin receptor type 2 (TFR2). In erythroid precursors, TFR2 facilitates the export of the erythropoietin receptor (EPOR) to cell surface, which ensures the survival and proliferation of erythroblasts. Although TFR2 has a crucial role in erythropoiesis regulation, its mechanism of action remains to be clarified. To understand its role better, we aimed at identifying its protein partners by mass‐spectrometry after immunoprecipitation in erythroid cells. Here we report the kinase MRCKα (myotonic dystrophy kinase‐related CDC42‐binding kinase α) as a new partner of both TFR2 and EPOR in erythroblasts. We show that MRCKα is co‐expressed with TFR2, and TFR1 during terminal differentiation and regulates the internalization of the two types of transferrin receptors. The knockdown of MRCKα by shRNA in human primary erythroblasts leads to a decreased cell surface expression of both TFR1 and TFR2, an increased cell‐surface expression of EPOR, and a delayed differentiation. Additionally, knockout of Mrckα in the murine MEDEP cells also leads to a striking delay in erythropoiesis, showcasing the importance of this kinase in both species. Our data highlight the importance of MRCKα in the regulation of erythropoiesis.